2017
DOI: 10.1371/journal.pone.0189199
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate self-medication among adolescents and its association with lower medication literacy and substance use

Abstract: BackgroundWhile self-medication is common, inappropriate self-medication has potential risks. This study assesses inappropriate self-medication among adolescents and examines the relationships among medication literacy, substance use, and inappropriate self-medication.MethodIn 2016, a national representative sample of 6,226 students from 99 primary, middle, and high schools completed an online self-administered questionnaire. Multiple logistic regression analysis was used to examine factors related to inapprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
99
3
12

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(136 citation statements)
references
References 51 publications
4
99
3
12
Order By: Relevance
“…While home treatment is common it carries risks, whether individuals use medicines inappropriately, or whether its practice increases the delay in consulting a healthcare professional to receive appropriate care [28, 29]. Prompt diagnosis and treatment is the most effective means of preventing a mild case of malaria from developing into severe disease with increased risk of death [30].…”
Section: Discussionmentioning
confidence: 99%
“…While home treatment is common it carries risks, whether individuals use medicines inappropriately, or whether its practice increases the delay in consulting a healthcare professional to receive appropriate care [28, 29]. Prompt diagnosis and treatment is the most effective means of preventing a mild case of malaria from developing into severe disease with increased risk of death [30].…”
Section: Discussionmentioning
confidence: 99%
“…It can serve as an important predictor of rational medication use (Raynor, 2008;Cordina et al, 2018). Some studies have shown that a large proportion of medication-related adverse events would be preventable with better medication literacy (Zhong et al, 2016;Lee et al, 2017;Zheng et al, 2017). However, the associations between medication literacy and medication adherence have not been clearly explained.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of the present study, the drugs used by the women for self-medication were mostly for the treatment of colds and included, respectively, analgesics, antibiotics, anti-allergy drugs, and hypnotics; the results were more or less similar to those of other studies. For instance, in a previous study, cold and coughing were the most common causes of self-medication (38), and in another study, self-medication drugs used among adolescents consisted of non-steroidal antiinflammatory drugs (NSAIDs) or analgesics, cold stop and anti-cough drugs, anti-allergy drugs, and anti-acids (39). In another study conducted in Iran, herbal medicines had the highest rate, followed by analgesics and antibiotics, in the self-medication program of the people (37).…”
Section: Discussionmentioning
confidence: 97%
“…A study has reported that more than half of the people in India believed that selfmedication was often healing (40). However, the incidence of self-medication in other environments like the public population of Ardebil City, Iran, and European countries was 45.8% (39) and 61.6% (37), respectively. The higher incidence of selfmedication behaviors in the present study was likely related to the nature of the research community (women), as the results of numerous studies indicated the higher incidence of selfmedication among women compared to men (17,41).…”
Section: Discussionmentioning
confidence: 99%